The Digital Era and Muhammadiyah Education: Da'wah Communication as an Innovative Strategy in Islamic Learning - Abu Hanifah; Yaser Arafat; Titin Yenni; Ayu Munawaroh; Ramadoni, Muhamad Afdoli; Ahmad Jumhan (Wardah, 2025)
This study examines Muhammadiyah's educational reform in facing the challenges of the digital era. Digital transformation has fundamentally changed the educational paradigm, requiring Islamic educational institutions to adapt without losing their religious identity. This research used a qualitative approach with a case study method in several Muhammadiyah educational institutions. Data were collected through in-depth interviews, observations, and documentation studies. The results indicate that Muhammadiyah's educational reform in the digital era includes: (1) integrating digital technology into learning while maintaining progressive Islamic values, (2) developing the competencies of digital teachers and education personnel, (3) transforming the curriculum to meet the needs of the times, and (4) strengthening digital literacy based on Islamic and Muhammadiyah values. This study recommends the need for synergy between technological innovation and strengthening Islamic character in the implementation of Muhammadiyah's educational reform.